Pluralism As A Social Reality According To Islamic Thought - Bukhori, Imam; Zaeni, Akhmad; Agustin, Chunainah (UAS PRESS, 2025)
Pluralism is a necessity in human life. Pluralism or pluralism or diversity is a sunnatullah that must be contemplated and believed by every ummah, religious awareness is the key to sustainability in carrying out their respective religions. Pluralism also very often triggers conflict in society. Not infrequently these conflicts occur in the name of religion or other things that are inherent in a certain person or group. How then Islam views a form of plurality that exists in society is an interesting thing to discuss. This article will discuss this comprehensively by using descriptive qualitative methods and using library research methods, namely based on previous publications. The conclusion in this article is that Islam has given a set of demands on how to address pluralism or plurality in life. One of them is tolerance. However, with certain limits, namely by not mixing tolerance with the beliefs of each person.